(untitled) (Heritage, 2020)
Parallel worlds, alternative reality, interspace, these are the elements that are very noticeable in the works of Haruki Murakami. The other world is a place where its protagonists go in the hope that they will find the truth about themselves there. The search for identity, multiple personality disorder, alienation, loneliness, lack of inventiveness and the problems of modern society are refracted through the prism of parallel worlds that he creates in his works. Lost in the whirlpool of hopelessness, with blurred emotions that are triggered by the harsh reality of life, his characters find their place in that distorted picture of reality. This paper deals with the study of parallel worlds as a phenomenon that Haruki Murakami uses when he sculpts his characters and shapes his novels. The novels The Wind-Up Bird Chronicle, 1Q84 and The Norwegian Wood have been analyzed. Parallel worlds into which Murakami’s protagonists enter have been presented, as well as alternative reality as a mechanism for completing the image of a human being and his life phases.